Evolusi Padadigmatik Kesetaraan Gender Terhadap Pertumbuhan Ekonomi Tahun 2018-2022 Kabupaten/Kota Sumatera Utara - Oktania, Ainur; Suharianto, Djoko (FEB Universitas Sultan Ageng Tirtayasa, 2024)
This study aims to analyze the impact of gender equality on economic growth in 33 districts/cities in North Sumatra Province over the period 2018-2022. Three dimensions of gender equality are explored, namely education (represented by average years of schooling), health (represented by Life expectancy), and employment (represented by labor force participation rate). PaneldatawereanalyzedusingtheFixedEffect data were analyzed using the fixed effect model (FEM). The results show that gender equality in health has a positive and significant effect on economic growth, while gender equality in education and employment has a positive but statistically insignificant effect. The policy implications of this study discuss the importance of strengthening the contribution of gender equality to economic development and community welfare. These findings are reinforced by human capital theory, health economics theory, and gender division of labor theory.